A global potpourri of poisons - Abd Razak, Dzulkifli (1997)
HERE'S A QUICK LOOK AT POISONING cases that took place globally in 1996. The United States In Colorado, five men, who were enjoying themselves drinking beer and listening to music inside a cat at their garage with the engine on, died of poisoning of carbon monoxide fumes. Two American teachers nearly became victims of poisoning by their students. In one case, a 12yearold girl poured rat poison in her teacher's soda and was subsequently sentenced to five years detention. In another case, a teenager was charged with spiking his teacher's drink with the drug LSD. Both teachers suffered no harm. In Fort Lauderdale, a mother will be charged for having deliberately poisoned her nineyearold daughter by injecting faecal bacteria into her blood.